Membangun Sistem Hukum Pancasila Yang Merdeka Dari Korupsi Dan Menjunjung Hak Asasi Manusia (Ham) - Faturohman Faturohman; Alvya Anggreini; Revina Tri Deasti (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Developing a legal system based on Pancasila that is free from corruption and upholds human rights (HAM) is an important challenge in strengthening the foundations of democracy and justice in Indonesia. A legal system based on Pancasila values ​​must be able to provide fair and equitable protection for all citizens in the country, while maintaining independence from corrupt practices that damage and affect the integrity of legal institutions. On the other hand, upholding Human Rights (HAM) must also be a top priority in efforts to ensure justice and dignity for every individual. In achieving these goals, concrete steps need to be taken. Firstly, in-depth legal reform is needed to align legal regulations with Pancasila values, strengthen the independence of law enforcement institutions, and increase transparency and accountability in the justice system. Second, eradicating corruption must be the main focus, by implementing very strong anti-corruption policies, strengthening law enforcement institutions, and encouraging active community participation in monitoring and preventing corruption. In addition, the government's efforts to protect Human Rights (HAM) must be increased through strict law enforcement against human rights violations, strengthening institutions for the protection of Human Rights (HAM), and increasing public awareness about human rights. This is important to ensure that every individual has equal access to justice and legal protection, without discrimination or oppression.